Anterior Inferior Cerebellar Aneurysm Treated by Aneurysm Resection and Intracranial Artery Anastomosis in situ: A Case Report and Literature Review - Huang, Chaojue; Qin, Shixing; Huang, Wei; Yu, Yongjia (Frontiers in Surgery, 2021)
Background: Anterior Inferior Cerebellar Artery (AICA) aneurysms are relatively rare in clinical practice, accounting for less than 1% of all intracranial arteries. After the diagnosis and location are confirmed by angiography, magnetic resonance and other imaging examinations, interventional or surgical treatment is often used, but some complex aneurysms require reconstructive surgery. Case Description: An 8-year-old male child was admitted to the hospital due to sudden disturbance of consciousness for 2 weeks. The head CT showed hematocele in the ventricular system with subarachnoid hemorrhage in the basilar cistern and annular cistern. On admission, he was conscious, answer correctly, neck soft, limb muscle strength was normal, no cranial nerves and nervous system abnormalities. Preoperative examination showed the right side of the anterior distal arteries class under the circular wide neck aneurysm, the distal anterior inferior cerebellar artery supplies a wide range of blood to the cerebellum, the ipsilateral posterior inferior cerebellar artery is absent and the aneurysm get close to the Ⅶ、Ⅷ nerves. The aneurysm was successfully treated by aneurysm resection and intracranial artery anastomosis in situ of a2 AICA-a2 AICA. Conclusions: Anterior Inferior Cerebellar Artery (AICA) aneurysms are relatively rare, in this case, a complex wide-necked aneurysm was successfully treated by aneurysm resection and anastomosis in situ of a2 AICA-a2 AICA. This case can provide a reference for the surgical treatment of complex anterior cerebellar aneurysms.